Poincaré Work on Celestial Mechanics: Predictability versus Determinism in the Context of Restricted Three-Body Problem - Laureano, M.; Ferreira, M. A. M. (arXiv:2212.12339, 2025)
The publication of Principia Mathematica in 1678 by Newton became known the celestial bodies motion laws, which characterize the Classical Mechanics. Thereafter made sense to search about the movement of these bodies from known initial conditions, particularly in the 3 body problem. In this paper it is exposed the influence of Poincaré work, in 1880, in this problem on the beginning of Deterministic Chaos Theory based on the development of several new qualitative tools. The application of such tools led him to the discovery of a special kind of behavior: the dynamical instability. Contrary to the common idea that this kind of behavior was first evidenced by Lorenz in 1963, the Poincaré theoretical research was sufficiently clear about the existence of chaotic deterministic behavior. Until the time of Poincaré, there was a tacit assumption that the uncertainty in the output does not arise from any randomness in the dynamical laws, since they are completely deterministic, but rather from the lack of the infinite accuracy in the initial conditions. In this paper it is emphasized that the issues of determinism and predictability are distinct.